2014
DOI: 10.1002/ejoc.201301667
|View full text |Cite
|
Sign up to set email alerts
|

Cyclocondensation of Hydroxylamine with 1,3‐Bis(het)arylmonothio 1,3‐Diketones and 1,3‐Bis(het)aryl‐3‐(methylthio)‐2‐prop­enones: Synthesis of 3,5‐Bis(het)arylisoxazoles with Complementary Regioselectivity

Abstract: Efficient routes for the regioselective synthesis of 3,5-bis-(het)arylisoxazoles with complementary regioselectivity have been developed. The methods involve the cyclocondensation of hydroxylamine hydrochloride with either 1,3-bis(het)arylmonothio-substituted 1,3-diketones 1 or with 3-methylthio-1,3-bis(het)aryl-2-propenones 2 under various reaction conditions. In the first protocol, diketones 1 were treated with hydroxylamine hydrochloride in the presence of sodium acetate/acetic acid (pH 2.2) in refluxing et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Of most interest, Singh reported the synthesis of 3‐amino‐5‐substituted isoxazoles via condensation of β‐oxo‐dithioesters, an amine and hydroxylamine (Scheme ) 87. Rangappa and Ila reported the regioselective synthesis of 3,5‐disubstittued isoxazoles from monothio‐β‐diketones and hydroxylamine hydrochloride in the presence of base (Scheme B) 88. Dong developed an efficient synthesis of 5‐amino‐3,4‐disubstituted isoxazoles from cyclopropyl oximes using POCl 3 under mild conditions (Scheme C) 89…”
Section: Synthesis Of Isoxazoles Via Condensation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of most interest, Singh reported the synthesis of 3‐amino‐5‐substituted isoxazoles via condensation of β‐oxo‐dithioesters, an amine and hydroxylamine (Scheme ) 87. Rangappa and Ila reported the regioselective synthesis of 3,5‐disubstittued isoxazoles from monothio‐β‐diketones and hydroxylamine hydrochloride in the presence of base (Scheme B) 88. Dong developed an efficient synthesis of 5‐amino‐3,4‐disubstituted isoxazoles from cyclopropyl oximes using POCl 3 under mild conditions (Scheme C) 89…”
Section: Synthesis Of Isoxazoles Via Condensation Reactionsmentioning
confidence: 99%
“… A: 3‐Amino‐5‐substituted isoxazoles from β‐oxo‐dithioesters by Singh 87. B: 3,5‐Disubstituted isoxazoles from monothio‐1,3‐diketones by Ila et al 88. C: 5‐Amino‐3,4‐disubstituted isoxazoles from cyclopropyl oximes by Deng 89…”
Section: Synthesis Of Isoxazoles Via Condensation Reactionsmentioning
confidence: 99%
“…Purification by flash column chromatography (SiO 2 , gradient: Hex – 95:5 Hex/AcOEt – 9:1 Hex/AcOEt) affords the title compound as a white solid: 18 mg, 71 %. 1 H (500 MHz, CDCl 3 ) δ: 7.85–7.84 (m, 2H), 7.76–7.75 (m, 2H), 7.46–7.43 (m, 3H), 6.98–6.97 (m, 2H), 6.69 (s, 1H), 3.84 (s, 3H). 13 C (125 MHz, CDCl 3 ) δ: 170.6, 163.1, 161.3, 130.1, 129.5, 129.1, 127.6, 127.0, 120.5, 114.6, 96.3, 55.6.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, Ila and co-workers explored the regioselective synthesis of 3-isoxazolylindoles via the cyclocondensation of hydroxylamine hydrochloride with 1-aryl-3-(1-methylindol-3-yl)-3thioxopropan-1-ones and (Z)-1-aryl-3-(1-methylindol-3yl)-3-(methylthio)prop-2-en-1-ones under various conditions. 9 They found that 3-(isoxazol-3-yl)indoles were only obtained in good yields when the cyclocondensation reaction of hydroxylamine hydrochloride with 1-aryl-3-(1-methylindol-3-yl)-3-thioxopropan-1-one was carried out in the presence of NaOAc in a boiling mixture of acetic acid, benzene, ethanol, and water (1:1:0.5:0.1; pH 2.2). while the reaction of hydroxylamine hydrochloride with (Z)-1-aryl-3-(1-methylindol-3-yl)-3-(methylthio)…”
mentioning
confidence: 99%
“…prop-2-en-1-one yielded isomeric 3-(isoxazol-5-yl)indoles in the presence of Ba(OH) 2 in refluxing EtOH. 9 Although this method was quite useful to access the target compounds, its limitations are the use of distinct precursors and electrophilic solutions [NaOAc vs Ba(OH) 2 ]. Some other useful methods, including iterative assembly of nitrile oxides with ynamides, 10 electrophilic cyclization of (Z)-O-methyloximes, 11,12 [3+2] cycloaddition of nitrile oxides and arynes, 13,14 iminoxyl radical facilitated regioselective cyclization of -halo-,-and -halo-,-unsaturated ketoximes 15 have also been developed for the regioselective synthesis of 3-(isoxazol-3-yl)indoles.…”
mentioning
confidence: 99%